Immune-related adverse events of biological immunotherapies used in COVID-19 - Baracaldo-Santamaría, Daniela; Barros-Arias, Giovanna María; Hernández-Guerrero, Felipe; De-La-Torre, Alejandra; Calderon-Ospina, Carlos-Alberto (Frontiers in Pharmacology, 2022)
The use of biological immunotherapeutic drugs is one of the options currently being evaluated and employed to manage COVID-19, specifically monoclonal antibodies, which have shown benefit by regulating the excessive immune response seen in patients with severe infection, known as a cytokine storm. Tocilizumab has received particular importance for this clinical application, as has Sarilumab. Both drugs share a substantial similarity in terms of pharmacodynamics, being inhibitors of the interleukin six receptor (IL-6R𝛼). Furthermore, Sotrovimab, a neutralizing anti-SARS CoV-2 antibody, has gained the attention of the scientific community since it has recently been authorized under certain circumstances, positioning itself as a new therapeutic alternative in development. However, despite their clinical benefit, biological immunotherapies have the potential to generate life-threatening immune-related adverse events. Therefore it is essential to review their incidence, mechanism, and risk factors. This review aims to provide a comprehensive understanding of the safety of the biological immunotherapeutic drugs currently recommended for the treatment of COVID-19, provide a review of the known immune-mediated adverse events and explore the potential immune-related mechanisms of other adverse reactions.